TRANSFORMASI BUDAYA SEKOLAH: STRATEGI KEPALA SEKOLAH DALAM MENCIPTAKAN LINGKUNGAN PENDIDIKAN YANG INKLUSIF DAN DIRINDUKAN - Anton Setiabudi; B. Herawan Hayadi; Minkhaermidah Minkhaermidah; Euis Fidyana; Siti Mutmainah (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
This study aims to explore and analyze the strategic role of school principals in transforming school culture toward an inclusive and "longed-for" educational environment. In the modern era of education, schools are often trapped in fulfilling administrative standards, causing them to lose their humanistic side. This study employs a qualitative approach with a case study method to investigate how a principal's policies and leadership style influence the emotional climate of the school. The findings indicate that successful cultural transformation is rooted in three key strategies: the implementation of empathy-based transformational leadership, the creation of inclusivity policies that embrace diverse student characters, and the development of school rituals that build emotional closeness (such as the culture of greeting and appreciation). These findings conclude that when a principal succeeds in building a psychologically safe and inclusive ecosystem, the school is no longer merely a place for formal learning, but becomes a second home longed for by all school members. This research contributes to the development of school leadership models that focus on the emotional well-being of both students and teachers.